Stabilization of the dynamic behavior of a UNIPOL process for polyethylene production - Ghasem, Nayef Mohamed; Hussain, Mohd Azlan (Curtin University of Technology, 2004)
Polyolefins have become one of the most important plastics worldwide due to continuous improvements in catalysts and processes. Gas-phase polymerization of olefins is one of the most important polymerization processes. Compared to other processes such as slurry and solution polymerization, gas-phase processes have many distinct advantages, e.g. reduced capital and operating costs. Moreover, gas-phase polymerization offers a large variety of products, which could not be produced by other processes. However, sheeting and agglomeration of polymer particles are two serious problems, which can occur in modern gas-phase polymerization processes. Overheating of particles may occur due to very high reaction rates. The temperature of a particle can then rise above the softening temperature. In this work, recent theories of bifurcation and chaos are used to analyze the dynamic behavior of the UNIPOL process for the gas-phase production of polyethylene using a Ziegler-Natta catalyst. The dynamic behavior covers a wide range of the design and operating parameters domain for this industrially important unit. A conventional proportional-integral-derivative (PID) controller was implemented to stabilize the desired operating point on the unstable steady-state branch to a certain range of catalyst injection rate. By contrast, it was found that the controlled process can go through a period doubling sequence leading to chaotic strange attractors. The practical implications of this analysis can be very serious, since chaos is shown to exist close to the desired operating point where high polyethylene production rates can be achieved.